Apuntes introductorios sobre los fundamentos de la responsabilidad patrimonial de la Administración Pública - Villalobos Villalobos, Vicente Brayan (2022)
The patrimonial responsibility of the State is an issue belonging to the general part of administrative law. In Peruvian law, this institution does not have a clear and deep theoretical development as the civil liability system applied in private law does. Through this paper, the author outlines some generic considerations on the foundations of the duty to compensate by the Public Administration, generated when, in the exercise of its legally attributed powers, it causes injuries to the legally protected interests of the administered. Thus, the purpose of this work is to establish an approximation at the national headquarters on the theory of the patrimonial responsibility of the State, without prejudice to recognizing the influence of some institutions of private law.